Enhancing Creative Content in Education Delivery Utilising Multimedia Applications - Diong, Jia Xin; Soon, Eu Hui; Tan, Foong Ping; Xu, Jinsongzi (INTI International University, 2024)
The shift to online education due to the Covid-19 pandemic has transformed the delivery of educational content, a practice that continues in most higher education institutions. This study investigates how multimedia applications can improve the way innovative information is delivered in the classroom. To get information about their online learning experiences, 120 university students participated in online surveys and interviews using a quantitative methods approach. The study investigates the difficulties students encounter in reaching successful learning objectives and how these difficulties relate to the information learned through online means, as opposed to inperson lectures. Results show that students' focus and participation in online classrooms are greatly impacted by technological obstacles, such as subpar gadgets and erratic internet connections. These observations highlight the necessity of utilising multimedia applications and addressing technology constraints in order to enhance the educational process and close the gap between traditional classroom settings and online learning environments. This research outcome strongly addresses the targets within Sustainable Development Goals 12 (SDG 12).